Repetitive RNAs as regulators of chromatin-associated subcompartment formation by phase separation - Frank, Lukas; Rippe, Karsten (Journal of molecular biology, 2020)
Repetitive RNA (repRNA) sequences emerge as important regulators of the dynamic organization of genomic loci into membrane-less subcompartments with distinct nuclear functions. These domains include sites of active transcription like the nucleolus as well as (peri)centromeric and telomeric satellite repeats. Recent studies point to an important role of repRNAs in complex with proteins to promote a phase separation-driven formation of chromatin domains. We review how key features of the phase separation process can be revealed by different experimental approaches and discuss the associated structure-function relationships for chromatin subcompartments that involve repRNA.